Comparison of intraocular pressure measurements with different contact tonometers in young healthy persons - Saulius Galgauskas; Rasa Strupaite; Ernesta Strelkauskaite; Rimvydas Asoklis (International Journal of Ophthalmology, 2016)
AIM: To analyze the correlation of Goldmann applanation tonometer (GAT), I-Care tonometer and Tono-Pen tonometer results in young healthy persons, and to investigate the influence of central corneal thickness (CCT) on intraocular pressure (IOP) measurements recorded with these tonometers. METHODS: We conducted a pilot clinical study in 78 eyes of 78 subjects aged 22-28 years old (44 women and 34 men; mean age 23.8±1.19y). IOP was measured using GAT, I-Care and Tono-Pen tonometers, followed by measurements of CCT. Statistical analysis was performed using SPSS 20.0. RESULTS: The mean IOPs and standard deviation (±SD) for GAT, I-Care and Tono-Pen were 15.62±2.281 mm Hg, 16.29±2.726 mm Hg and 16.32±2.393 mm Hg, respectively. The mean CCT was 555.15±29.648 μm. Clear positive correlations between GAT and I-Care, GAT and Tono-Pen, and I-Care and Tono-Pen tonometers were found (r=0.867, P<0.001; r=0.861, P<0.001; r=0.915, P<0.001, respectively). In comparison between devices, Bland–Altman analysis showed a significant mean difference (MD) in the measurements by GAT and I-Care of −0.679 mm Hg and by GAT and Tono-Pen of −0.705 mm Hg ( P<0.001), but there was no significant difference between I-Care and Tono-Pen ( P>0.05). Both non-gold standard tonometers were affected by CCT; that is, both I-Care and Tono-Pen tonometer values were significantly higher with higher CCT means (>555 μm; MD=−1.282, P<0.001; MD=−0.949, P<0.001, respectively) compared with GAT. CONCLUSION: Both I-Care and Tono-Pen tonometers overestimated IOP compared with the GAT values. Either the I-Care or Tono-Pen tonometer could be used instead of GAT because there was no significant difference between their results. Higher CCT values (>555 μm) were associated with overestimated IOP values.